2020
DOI: 10.1186/s12872-020-01797-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the prevalence of hypertension and its associated risk factors in a population-based study: Fasa PERSIAN COHORT data

Abstract: Background A high prevalence rate of hypertension (HTN) and its subsequent serious complications made this disease a major health-treatment concern in many societies. The current study aimed to investigate the prevalence of hypertension and its associated risk factors in Fasa PERSIAN COHORT in south of Iran in 2019. Methods This was an analytical-cross sectional study. The study population were the individuals covered by Fasa cohort. Information of the first phase of Fasa Persian cohort in south of Iran was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“… 32 Relatively higher BP was reported in the Fasa cohort study in 2020. 10 The authors have reported a prevalence of 16.1% for stage 1 HTN and 17.9% for stage 2. In more detail, systolic HTN had a prevalence of 7.6% and 7.6% in men and 8.5% and 10.3% in women for stages I and II, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 32 Relatively higher BP was reported in the Fasa cohort study in 2020. 10 The authors have reported a prevalence of 16.1% for stage 1 HTN and 17.9% for stage 2. In more detail, systolic HTN had a prevalence of 7.6% and 7.6% in men and 8.5% and 10.3% in women for stages I and II, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The first and the second stages of HTN were detected in 16.1% and 17.9% of the population, respectively. 10 In a meta-analysis by Afsargharehbagh et al , 11 including 48 studies on 417 392 individuals, pre-HTN and HTN had an overall prevalence rate of 31.6% and 20.4%, respectively. 11 …”
Section: Introductionmentioning
confidence: 99%
“…The people who were Overweight and obesity have special clinical metabolic types, and can cause various diseases including hypertension, diabetes, lipid disorders, cardiovascular diseases and various types of malignant tumors. Overweight and obesity are themselves a risk factor for hypertension [6,13] . Whether they are healthy metabolism or unhealthy metabolism, the risk of cardiovascular diseases including hypertension is very high [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obese people have special clinical metabolic characteristics and complications, including hypertension, diabetes, lipid disorders, cardiovascular diseases, and various types of malignant tumors [12] . Overweight and obesity are risk factors for hypertension [6,13] , and the risk of cardiovascular diseases is high in people with healthy or unhealthy metabolic states [14,15] . The overweight and obese populations have different clinical and metabolic characteristics; therefore, the risk factors for hypertension in overweight and obese people and their interactions should be explored from the perspective of etiology.…”
Section: Discussionmentioning
confidence: 99%